Strategi Pengembangan Destinasi Wisata Embung Popoan melalui Destination Branding di Desa Kepohagung, Tuban - Ata Amrullah; Siti Alfiatur Rohmaniah; Miko Tri Afandi (Pusat Riset dan Inovasi Nasional, 2025)
This community service project aimed to empower the Kepohagung Village community by optimizing Embung Popoan's tourism potential through a comprehensive destination branding strategy. Despite its significant natural appeal, the destination was underdeveloped due to a lack of directed image management, resulting in low visitor numbers and limited local economic impact. Employing a participatory action research method, the team collaborated with local stakeholders to design and implement a new visual identity, including a distinct logo, interactive tourism map, and a compelling tagline. Furthermore, a robust digital promotional ecosystem was developed, featuring a user-friendly interactive website and physical merchandise. Preliminary post-implementation assessment revealed a significant increase in public and visitor awareness; early data indicated an estimated 20% rise in visitor inquiries and a 15% increase in social media engagement within the first two months. Visitor feedback highlighted improved information clarity and enhanced destination attractiveness. This initiative not only diversified local economic activities through merchandise sales but also fostered a stronger sense of local ownership, directly contributing to sustainable tourism development and community welfare in Kepohagung Village.